First results of the EORTC-SPECTA/Arcagen study exploring the genomics of rare cancers in collaboration with the European reference network EURACAN. Issue 6 (1st December 2020) - Morfouace, Marie; Stevovic, Aleksandra; Vinches, Marie; Golfinopoulos, Vassilis; Jin, Dexter X.; Holmes, Oliver; Erlich, Rachel; Fayette, Jerome; Croce, Sabrina; Ray-Coquard, Isabelle; Girard, Nicolas; Blay, Jean-Yves
Abstract : Purpose: Rare cancers are defined by an incidence of <6 out of 100 000 cases per year. They are under-represented in clinical research including tumour molecular analysis. The aim of Arcagen is to generate a multinational database integrating clinical and molecular information of patients with rare cancers. Patients and methods: We present the retrospective feasibility cohort of patients with rare cancers, with previously collected tumour samples available from any stage. Molecular analysis was performed using FoundationOne CDx for all histologies except for sarcoma where FoundationOne Heme was used. Clinical data including demographic data, medical history, malignant history, treatment and survival data were collected. Results: Eighty-seven patients from three centres were screened; molecular data were obtained for 77 patients (41 sarcomas, 9 yolk sac tumours, 14 rare head and neck cancers, 13 thymomas). The median age at the time of diagnosis was 48 (range 28–85). Most patients had reportable genomic alterations (89%). The most common alterations were linked to cell cycle regulation (TP53, RB1, CDKN2A/B deletions and MDM2 amplification). Multiple activating single-nucleotide variants (SNVs) could be detected in the RAS/RAF family. The tumour mutational burden status was globally low across all samples with a median of 3 Muts/MB (range 0–52). Only 4 cases (ie, 4.7% of tumours) had direct actionable mutations for a treatment approved in Europe within the patient's tumour type. Conclusion: The Arcagen project aims to bridge the gap and improve knowledge of the molecular landscape of rare cancers by prospectively recruiting up to 1000 patients.